2022
DOI: 10.1002/bse.3284
|View full text |Cite
|
Sign up to set email alerts
|

Carbon emissions trading and corporate green investment: The perspective of external pressure and internal incentive

Abstract: The carbon emissions trading scheme (CETS) is an important institutional innovation that internalizes external costs caused by corporate carbon emissions and promotes firms to engage in green development. Based on a 2009–2019 sample of Chinese enterprises of heavily polluting industries listed on the Shanghai Stock Exchange (SSE) and Shenzhen Stock Exchange (SZSE), this paper employs the difference‐in‐differences model to examine the effect of CETS on corporate green investment and discuss the moderating effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 67 publications
0
5
0
Order By: Relevance
“…This thesis explores the impact of corporate green investment on carbon emission intensity at the micro level. Referring to previous studies on the determinants of carbon emissions, such as Chen et al [ 85 ] and Chen et al [ 86 ], which concluded that equity concentration has a negative impact on corporate fulfillment of environmental responsibility, and that the nature of equity also exerts a heterogeneous effect on corporate environmental behavior, this study includes the proportion of the top ten shareholders' shareholdings and the nature of equity as control variables. In addition, because it is firm-level data, we again control for firm-specific relevant variables, drawing on the studies of Albitaret al [ 87 ] and Gerged et al [ 88 ] on carbon emissions.…”
Section: Research Methods and Designmentioning
confidence: 99%
“…This thesis explores the impact of corporate green investment on carbon emission intensity at the micro level. Referring to previous studies on the determinants of carbon emissions, such as Chen et al [ 85 ] and Chen et al [ 86 ], which concluded that equity concentration has a negative impact on corporate fulfillment of environmental responsibility, and that the nature of equity also exerts a heterogeneous effect on corporate environmental behavior, this study includes the proportion of the top ten shareholders' shareholdings and the nature of equity as control variables. In addition, because it is firm-level data, we again control for firm-specific relevant variables, drawing on the studies of Albitaret al [ 87 ] and Gerged et al [ 88 ] on carbon emissions.…”
Section: Research Methods and Designmentioning
confidence: 99%
“…This presents a crucial environmental challenge that requires immediate attention [2]. The actions of both individuals and organizations are key factors contributing to the escalation of GHG emissions [3,4]. There are numerous adverse effects associated with climate change, including extreme weather events, that require proactive responses [1].…”
Section: Introductionmentioning
confidence: 99%
“…However, it is important to understand that there may be differences between expert users and regular users in their utilization of these platforms, as platforms tend to leverage the knowledge of expert users [12]. Equally important is the awareness of climate change in our daily lives and practices, including our reliance on digital technologies and information management, which have been recognized as crucial contributors to energy consumption and carbon emissions [3,13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conventional financing sources, such as banks and private investors, often shy away from these initiatives due to perceived risks and uncertainties. [6,7] However, GF offers incentives for enterprises to implement environmentally friendly practices. The introduction of GB has created a new avenue of financing dedicated to supporting long-term projects in the RE sector.…”
mentioning
confidence: 99%